Clinical and Doppler Study of Restrictive Filling Pattern in Patients with Dilated Cardiomyopathy - Ali A Mohammed Al Mousawi; Nezar Naser Al Attabi; Hassan Ali Farhan (مجله كليه طب الكندي, 2013)
Background: Dilated cardiomyopathy (DCM) is a well-recognized cause of cardiovascular morbidity and mortality.Objectives: To evaluate the prognostic implications of the restrictive left ventricular filling pattern (RFP) in dilated cardiomyopathy.Methods: Patients with DCM admitted to Ibn AL-Bitar Hospital for Cardiac Surgery, Baghdad-Iraq, from May 2006 to August 2008, underwent a full clinical evaluation and Doppler echocardiography study. Patients were classified into three groups: Group I had persistent restrictive filling pattern; Group II had reversible restrictive filling pattern; and Group III had nonrestrictive filling pattern. Results: The current study was conducted on a total number of 80 patients with DCM, fifty (62.5 %) were males and 30(37.5%) were females with a male to female ratio 1.6:1. Patients with restrictive filling pattern (Group I&II) were 51 (63.8%), while patients with nonrestrictive filling pattern (Group III) were 29 (36.2%). During follow up, patients with persistent restrictive filling pattern (30; 37.5%) had higher New York Heart Association (NYHA) class symptoms, low ejection fraction (EF) and higher mortality; 6 (20%) died within the first year, 6 (20%) died in the second year. Clinical improvement was significantly frequent in Group II and III than Group I.Conclusions: In patients with DCM, the persistence of restrictive filling at 3 months is associated with a high mortality the patients with reversible restrictive filling have a high probability of improvement and excellent survival.